2015
DOI: 10.15604/ejef.2015.03.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Pension Fund Performance in East Asia: A Comparative Study

Abstract: This paper discusses and analyzes asset allocation and performance of the major pension funds in four East Asia countries, namely Malaysia, Singapore, Hong Kong and South Korea. The respective funds for these countries are Employee Provident Fund (EPF), Central Provident Fund (CPF), Mandatory Pension Fund (MPF) and National Pension Service (NPS). The impact of some economic crises on the fund performance will also be assessed. Besides looking at the individual countries, a comparison of the performance among a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…By employing the same methodology, Duggimpudi et al (2010) [23] find evidence for well-diversified funds that exhibit higher performance than the market. This is in tandem to Ahmad and Nor (2015) [20], who find that the main pension funds in Malaysia, Singapore, Hong Kong and South Korea all had a negative real return. Moreover Drobetz and Kohler (2002) [24], by studying fifty-one German and Swiss balanced mutual funds, attribute over 80% of returns' variability to asset allocation.…”
Section: Literature Reviewmentioning
confidence: 60%
See 1 more Smart Citation
“…By employing the same methodology, Duggimpudi et al (2010) [23] find evidence for well-diversified funds that exhibit higher performance than the market. This is in tandem to Ahmad and Nor (2015) [20], who find that the main pension funds in Malaysia, Singapore, Hong Kong and South Korea all had a negative real return. Moreover Drobetz and Kohler (2002) [24], by studying fifty-one German and Swiss balanced mutual funds, attribute over 80% of returns' variability to asset allocation.…”
Section: Literature Reviewmentioning
confidence: 60%
“…Since the pioneering work of Sharpe (1992) [9], there has been a growing literature focusing on assessing the style analysis of mutual funds globally (see for instance: Lobosco and DiBartolomeo (1997) [10], Gallo et al (1997) [11], Cai et al (1997) [12], Bassett and Chen (2002) [13], Amenc et al (2003) [14], Agudo and Marzal (2004) [15], Papadamou and Siriopoulos (2004) [16], Białkowski and Otten (2011) [17], Bailey and Lopez de Prado (2012) [18], Lean et al (2015) [19], Ahmad and Nor (2015) [20], Kim et al (2015) [21]). Nevertheless, this study is the first that particularly employs a style analysis to examine the effects of active management on Japanese mutual funds in the pre-and post-Lehman Brothers collapse period.…”
Section: Introductionmentioning
confidence: 99%
“…However, since only management fees were taken into consideration in this study, future research may also include sales fee, loading fee, redemption fee, and other fees to test the impact of different fee structure on the performance of pension funds. Lastly, future research may also incorporate the bond factorsterm and default premium in evaluating the performance of Growth Fund, since Fama and French [20] provides evidence on the common factors shared between equity and bond investments in an integrated market.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the performance of public pension funds was also compared among Asian countries. Ahmad and Nor [20]'s study on the public pension funds in Malaysia, Singapore, South Korea, and Hong Kong from the year 2000 to 2011 has found that Singapore's Central Provident Fund (CPF) is among the four pension funds that earns the highest return proxied by Return on Investment despite that it is the most conservative investment that invest primarily in the country's treasury securities. Meanwhile, Mandatory Pension Fund (MPF) in Hong Kong earns the lowest return being the most aggressive fund that invests largely in equity market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, they discovered that the determinants of fund performance differed between the USA and other world markets. In East Asia, Ahmad and Nor (2015) found that the real returns of four pension funds were negative. In addition, Tan (2015) found that Taiwanese fund managers were skilled in portfolio selection, as shown by the stellar performance of fifteen equity funds in the domestic market.…”
Section: Previous Studies a Comparison Of The Performance Of Imfs Anmentioning
confidence: 99%